Changes in the European Audit Services Market - Malgorzata KUTERA (Communications of International Proceedings, 2020)
In-depth changes are now taking place in the audit services market in Europe. They are mainly caused by the implementation of new rules laid down in European regulations. However, Member States have relatively broad freedom in drafting detailed regulations. In light of the above, the main purpose of this article is to identify disparities between financial audit systems in different European countries and to assess them in the context of changes introduced in the EU as a whole. Particular attention is paid to aspects connected with the organisation and the structure of the audit services market. Rules applicable in 30 countries have been analysed and differences identified concerning the scope of Public Interest Entities, the obligatory audit firm rotation, the ban on providing selected non-audit services, and joint audits. Disparities were found in key aspects of statutory auditor activities which are still very controversial. The biggest ones concern the obligatory auditor rotation and the maximum duration of engagement by a given entity. This has a negative impact on the effectiveness of the whole market and its competitiveness.
Keywords: Statutory Audit; EU Audit Reform; Audit Firm Rotation; Non-Audit Services.